Green awareness, sustainability knowledge, and perception of corporate environmental responsibility impacting sustainable investment preference - Muhammad Distian Andi Hermawan (EcoProfit: Sustainable and Environment Business, 2026)
Background: This study aims to analyze the influence of green awareness (GA), sustainability knowledge (SK), and perception of corporate environmental responsibility (PCER) on sustainable investment preferences in pawnshops, with perceived value as a mediating variable. The research background is based on the increasing public interest in green investment and Pegadaian's commitment to strengthening its sustainable product portfolio. This research was conducted on the people of Palembang City and Bandar Lampung as a representation of urban communities who are starting to be responsive to sustainability issues. Methods: The method used is a quantitative approach with the partial least square–structural equation modeling (PLS-SEM) technique. Data was obtained through questionnaires with public respondents who knew or used pawnshops services. The analysis was conducted to evaluate the direct and indirect relationships between variables, including testing the mediating effect of perceived value. Findings: The results of the study show that GA and SK have a positive but relatively small influence on sustainable investment preferences. PCER has a stronger influence than other variables, emphasizing the importance of public perception of corporate environmental responsibility in determining investment preferences. In addition, perceived value has proven to be a significant mediator, reinforcing the influence of GA, SK, and PCER on investment preferences. Conclusion: These findings confirm that perceived value perceptions play a central role in encouraging people to choose sustainability-oriented pawnshops investment products. This research provides strategic implications for Pegadaian to strengthen education, sustainability transparency, and product value communication in order to increase people's interest in green investment. Novelty/Originality of this article: The originality of this study lies in its expansion of the research on sustainable investment to the non-bank financial sector, specifically focusing on the product portfolio of pawnshops in Indonesia.